Rancang Bangun Aplikasi Pengolahan Nilai Rapor dengan Kurikulum 2013 di SMK Negeri 1 Cerme - Muhammad Ramzi; Jusak Jusak; Vivine Nurcahyawati (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Processing value of final report in SMK Negeri 1 Cerme should be based on the curriculum of 2013.  Problem that occurs in the curiculum 2013 is that every teacher  must delve with rules for marking process that is considered to be more difficult than the previous curriculum. In that curriculum, every subjects consist of several types marking, i.e marking for knowledge acceptance comprises of daily marking, mid term exam and final a lot of final. Second  marking for skill comprises of laboratorium marking, projects and portfolio. The last type of marking is the attitude marking that consist of observations, self-assessment, peer assessment. After having the value of knowledge, skills and attitude then do checking on the value of the minimum completeness criteria, if the value is in compliance then calculated the ledger value from all values. After the interval values are converted according to standards that have been defined on the SMK, which will be obtained predicate value and the value of the description.With the application for processing the value of report cards, is expected value will be arranged neatly, and can control the value easily, because there will be a notification regarding the value has not been entered. The headmaster also facilitated in monitoring development of value each lesson. While students will also easy to see the value they get from teaching and learning activities at this time.